Curiosity - Fouhey, James; Aquino, Jennifer (Ascent Audio, 2024)
Open yourself to new possibilities. Curiosity is a powerful tool for leaders. It can help you cope with complexity, learn from challenging conversations, build trust, and discover new perspectives. This book provides the expert research and advice you need to break free of your assumptions, strengthen your relationships, and see the world differently.
Online resource; title from title details screen (O'Reilly, viewed July 2, 2024)
Keywords: Curiosity; Emotional intelligence; Empathy; Self-consciousness (Awareness); Compassion; Curiosité; Intelligence émotionnelle; Empathie; Conscience de soi; empathy; Audiobooks; Livres audio